(untitled) (PANGEEA, 2025)
The analysis of distribution of archaeological excavations at Rosia Montana in context of the issuance of historical task. Considering the large amount of data that preventive archaeological research produces at a certain time and considering the irreversible nature of archaeological research, the data modelling and digital management possibilities available now can be used to obtain databases, associated maps, reports, analyses and so on.